Clinical Care Pathways in Andrology - Mulhall, John P.; Stahl, Peter J.; Stember, Doron S. (Springer New York : Imprint: Springer, 2014)
Clinical Care Pathways in Andrology provides a valuable resource for understanding clinical decision-making in the context of the predominant male reproductive and sexual disorders for which patients commonly seek evaluation and treatment. Conditions that are less well-known but can be severely bothersome to patients, such as penile sensory loss, are also presented. Based on clinical evidence and expert consensus, practical clinical care pathways are featured for each condition.  Each clinical care pathway consists of an algorithm that delineates the overall structure of decision-making for each condition, describes initial clinical presentations, and guides the reader through diagnostic testing and treatment.  Furthermore, the volume features annotations that develop key andrological concepts and provide explanations for each step in diagnosis and management.    Designed for clarity and ease of use, Clinical Care Pathways in Andrology is a practical and valuable reference for urologists, primary care physicians, and residents who are not specialty trained in andrology.